Investigation the Relationship between Professional Behavior and Job Well- Being among Nurses in Shahrekord\'s Educational Hospitals - reza jahanbazi; masoud lotfizadeh (Tehran University of Medical Sciences, 2019)
Background: Nursing is one of the health care base and nursing services are in effect on ill-health indicators. This study aimed to investigate the relationship between professional behavior and job well-being of nurses employed at two Shahrekord educational hospitals in 2018. Materials and Methods: This descriptive-analytic study was performed on nurses employing at two educational hospitals in Shahrekord. A total of 269 nurses in both sexes were selected using stratified random sampling method. The Goz standard professional questionnaire for nurses and the Demo and Paschoal Survival Questionnaire were used. Data were analyzed by SPSS22 software using independent t-test, ANOVA, Kolmogorov Smearnov, Pearson Correlation Coefficient and simple linear regression at a significant level of 0.05. Results: Mean age of the respondents was 33.2 years old, 48% were aged between 31 to 40 years old while 3% were aged more than 50 years old, 58% and 42%were female and male, respectively. The average score of professional behavior and job well-being were 17.8 ± 104.5 (moderate to high) and 89.3 ± 12.9 (moderate), respectively. Regression analysis revealed that per unit increasing in the nurses professional behavior, 0.661 units were added to job well-being; and also, there was a significant correlation between "professional behavior" and "job well-being" (R2=0.328). Conclusion: The comprehensive national plan should be designed paying more attention to creation of the necessary infrastructure to promote professional behavior which can be result in long-range consequences of job well-being improvement; also, promotion of job well-being components should be considered.